Calculation of parameters of elementary nanocrystals of liquid metals at melting temperature - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
Method of calculation and calculated values of parameters of elementary nanocrystals of liquid metals at melting temperature are given. It has been shown that radii of elementary nanocrystals are from 2 nm to 12 nm, and the number of atoms in each elementary nanocrystal varies from 2000 to 100000. This provides liquid metals with a high solidification rate and explains the abnormally high diffusion coefficient in liquid metals compared to solid metals.